Combining the induced pluripotent stem cell (iPSC) technology with chimeric antigen receptor (CAR)-based immunotherapy: recent advances, challenges, and future prospects - Alidadi, Mehdi; Barzgar, Haniyeh; Zaman, Mohammad; Paevskaya, Olga A.; Metanat, Yekta; Khodabandehloo, Elnaz; Moradi, Vahid (Frontiers in Cell and Developmental Biology, 2024)
After experiencing many ups and downs, chimeric antigen receptor (CAR)-T cell therapy has reached a milestone as an anti-cancer method, as evidenced by the increasing number of clinical trials and approved products. Nonetheless, there is a real need to optimize CAR-T cell therapy and overcome its existing limitations. The importance of cellular starting material for generating CAR-T cells is undeniable, as the current personalized manufacturing approach is the main roadblock to providing a fast, affordable, and standard treatment for patients. Thus, developing an off-the-shelf CAR-T product is a leading focus in adoptive cell therapy. Several biotech companies worldwide are focused on developing an off-the-shelf CAR-T product from allogeneic sources. Induced pluripotent stem cells (iPSCs) have unique characteristics, making them highly attractive among various allogeneic sources. IPSCs can be modified with CAR, undergo other intended gene manipulations, and then be differentiated into functional hematopoietic lineages with anti-cancer activity. Moreover, iPSCs provide an unlimited cell source, simplifying the setting of a standard treatment protocol by generating a homogenous population of resulting cells and reducing batch-to-batch inconsistency. In this review, we delve into the manufacturing of iPSC-derived CAR-T (iCAR-T) cells and discuss the path and challenges of their clinical translation. We also introduce some iPSC-derived cellular alternatives to conventional iCAR-αβ-T cells, including iCAR-T cells with a limited TCR diversity, iCAR-NK, iCAR-macrophages, and iCAR-neutrophils and discuss their relative advantages and disadvantages as well as their differentiation from iPSCs in compliance with cGMP. Finally, we reviewed iPSC-derived CAR-engineered cells being evaluated in clinical trials.